ARE THERE HEALTH DISPARITIES AMONG JORDANIAN OLDER ADULTS? PROPOSED INTERVENTIONS (PART II) - Audai Hayajneh (European Scientific Journal, ESJ, 2015)
Several factors including access to health care, and the cost, and quality of that health care are varied among the population of Jordanian citizens, including older adults. Furthermore, there is a paucity of both formal instruments devoted to screening health outcomes relevant to older adults in Jordan, and also desired outcomes following proposed interventions to enhance health outcomes in older adults. Several strategies will be proposed for implementation as guidelines for healthcare providers in this paper. In addition to those strategies, myriad of interventions mentioned in this paper are driven by theoretical or conceptual models, and might eventually contribute to the promotion of healthcare. Finally, such interventions could also be useful in terms of their desired health outcomes at the end of the predetermined interventions targeting older adults in Jordan.